Nonlinear response of vibrational conveyers with non-ideal vibration exciter: primary resonance - Alisverisci, G. F.; Bayiroglu, H.; Unal, G. (SPRINGER, 2012)
Vibrational conveyers with a centrifugal vibration exciter transmit their load based on the jumping method. The trough is oscillated by a common unbalanced-mass driver. This vibration causes the load to move forward and upward. The motion is substantially related to the vibrational parameters. The transition of the vibratory system for over resonance excited by rotating unbalances is important in terms of the maximum vibrational amplitude and the power requirement from the drive for the cross-over. The mechanical system depends on the motion of the DC motor. In this study, the working ranges of oscillating shaking conveyers with a non-ideal vibration exciter have been analyzed analytically for primary resonance by the method of multiple scales with reconstitution, and numerically. The analytical results obtained in this study have been compared with the numerical results, and have been found to be well matched.
Keywords: Centrifugal vibration exciter; Vibrational conveyers; Non-ideal vibrations; Method of multiple scales with reconstitution; Primary resonance; TRANSITION; Engineering; Mechanics